An Analysis of Clinical Knowledge, Absenteeism, and Availability of Resources for Maternal and Child Health : A Cross-Sectional Quality of Care Study in 10 African Countries - Di Giorgio, Laura; Evans, David K.; Lindelow, Magnus; Nguyen, Son Nam; Svensson, Jakob; Wane, Waly; Tarneberg, Anna Welander (World Bank, Washington, DC, 2020)
This paper assesses the quality of health care across African countries based on health providers' clinical knowledge, their clinic attendance, and drug availability, with a focus on seven conditions accounting for a large share of child and maternal mortality: malaria, tuberculosis, diarrhea, pneumonia, diabetes, neonatal asphyxia, and postpartum hemorrhage. With nationally representative, cross-sectional data from 10 countries in Sub-Saharan Africa, collected using clinical vignettes, unannounced visits, and visual inspections of facilities, this study assesses whether health providers are available and have sufficient knowledge and means to diagnose and treat patients suffering from common conditions amenable to primary health care. The study draws on data from 8,061 primary and secondary care facilities in Kenya, Madagascar, Mozambique, Nigeria, Niger, Senegal, Sierra Leone, Tanzania, Togo, and Uganda, and 22,746 health workers. These data were gathered under the Service Delivery Indicators program. Across all conditions and countries, health care providers were able to correctly diagnose 64 percent of the clinical vignette cases, and in 45 percent of the cases, the treatment plan was aligned with the correct diagnosis. For diarrhea and pneumonia, two common causes of under-five deaths, 27 percent of the providers correctly diagnosed and prescribed the appropriate treatment for both conditions. On average, 70 percent of health workers were present in the facilities to provide care during facility hours when those workers were scheduled to be on duty. Taken together, the estimated likelihood that a facility has at least one staff present with competency and the key inputs required to provide child, neonatal, and maternity care that meets minimum quality standards is 14 percent. Poor clinical knowledge is a greater constraint in care readiness than drug availability or health workers' absenteeism in the 10 countries. However, the paper documents substantial heterogeneity across countries.